Innovative hydrogen station operation strategies to increase availability and decrease cost - Kurtz, Jennifer, author; Bradley, Thomas, advisor; Willson, Bryan, committee member; Suryanarayanan, Siddharth, committee member; Ozbek, Mehmet, committee member (Colorado State University. Libraries, 2019)
Major industry, government, and academic teams have recently published visions and objectives for widespread use of hydrogen in order to enable international energy sector goals such as sustainability, affordability, reliability, and security. Many of these visions emphasize the important and highly-scalable use of hydrogen in fuel cell electric cars, trucks, and buses, supported by public hydrogen stations. The hydrogen station is a complicated system composed of various storage, compression, and dispensing sub-systems, with the hydrogen either being delivered via truck or produced on-site. As the number of fuel cell electric vehicles (FCEVs) on roads in the U.S. have increased quickly, the number of hydrogen stations, the amount of hydrogen dispensed, and the importance of their reliability and availability to FCEV drivers has also increased. For example, in California, U.S., the number of public, retail hydrogen stations increased from zero to more than 30 in less than 2 years, and the annual hydrogen dispensed increased from 27,400 kg in 2015 to nearly 105,000 kg in 2016, and more than 913,000 kg in 2018, an increase of nearly 9 times in 2 years for retail stations. So, although government, industry, and academia have studied many aspects of hydrogen infrastructure, much of the published literature does not address hydrogen station operational and system innovations even though FCEV and hydrogen stations have some documented problems with reliability, costs, and maintenance in this early commercialization phase. In general, hydrogen station research and development has lagged behind the intensive development effort that has been allocated to hydrogen FCEVs. Based on this understanding of the field, this research aims to identify whether integrating reliability engineering analysis methods with extensive hydrogen station operation and maintenance datasets can address the key challenge of station reliability and availability. The research includes the investigation and modeling of real-world hydrogen station operation and maintenance. This research first documents and analyzes an extensive dataset of hydrogen station operations to discover the state-of-the-art of current hydrogen station capabilities, and to identify performance gaps with key criteria like cost, reliability, and safety. Secondly, this research presents a method for predicting future hydrogen demand in order to understand the impact of the proposed station operation strategies on data-driven decision-making for low-impact maintenance scheduling, and optimized control strategies. Finally, based on an analysis indicating the need for improved hydrogen station reliability, the research applies reliability engineering principles to the hydrogen station application through development and evaluation of a prognostic health management system.
Keywords: demand; hydrogen; station; fueling; availability; reliability